Pharmacologically active microcarriers influence VEGF‐A effects on mesenchymal stem cell survival. Issue 1 (11th January 2013) - Penna, Claudia; Perrelli, Maria‐Giulia; Karam, Jean‐Pierre; Angotti, Carmelina; Muscari, Claudio; Montero‐Menei, Claudia N.; Pagliaro, Pasquale
Abstract Resistance of transplanted mesenchymal stem cells (MSCs) in post‐ischemic heart is limited by their poor vitality. Vascular‐endothelial‐growth‐factor‐A (VEGF‐A) as such or slowly released by fibronectin‐coated pharmacologically‐active‐microcarriers (FN‐PAM‐VEGF) could differently affect survival kinases and anti‐apoptotic mediator (e.g. Bcl‐2). Therefore VEGF‐A or FN‐PAM‐VEGF could differently enhance cell proliferation, and/or resistance to hypoxia/reoxygenation (H/R) of MSCs. To test these hypotheses MSCs were incubated for 6‐days with VEGF‐A alone or with FN‐PAM‐VEGF. In addition, MSCs pre‐treated for 24‐hrs with VEGF‐A or FN‐PAM‐VEGF were subsequently exposed to H/R (72‐hrs 3% O2 and 3‐hrs of reoxygenation). Cell‐proliferation and post‐hypoxic vitality were determined. Kinases were studied at 30‐min., 1‐ and 3‐days of treatment. Cell‐proliferation increased about twofold (P < 0.01) 6‐days after VEGF‐A treatment, but by a lesser extent (55% increase) with FN‐PAM‐VEGF (P < 0.05). While MSC pre‐treatment with VEGF‐A confirmed cell‐proliferation, pre‐treatment with FN‐PAM‐VEGF protected MSCs against H/R. In the early phase of treatments, VEGF‐A increased phospho‐Akt, phospho‐ERK‐1/2 and phospho‐PKCε compared to the untreated cells or FN‐PAM‐VEGF. Afterword, kinase phosphorylations were higher with VGEF, except for ERK‐1/2, which was similarly increased by both treatments at 3 days. Only FN‐PAM‐VEGF significantly increased Bcl‐2 levels. After H/R, lactate dehydrogenase release and cleaved Caspase‐3 levels were mainly reduced by FN‐PAM‐VEGF. While VEGF‐A enhances MSC proliferation in normoxia, FN‐PAM‐VEGF mainly hampers post‐hypoxic MSC death. These different effects underscore the necessity of approaches suited to the various conditions. The use of FN‐PAM‐VEGF could be considered as a novel approach for enhancing MSC survival and regeneration in hostile environment of post‐ischemic tissues.